Enteral Vs. Parenteral Nutrition: Advantages and Disadvantages - Duna Penn (Indonesian Pediatric Society, 1996)
The goal of nutritional support is to maintain or replete lean body mass, to support host defense mechanisms, to avoid specific nutritional deficiencies, and in general to improve clinical outcome in a malnourished patient or in at risk to develop mal- nourishment. Nutritional support can be instituted by enteral or parenteral route; each has its advantages and disadvantages. Which mode of delivery is chosen much depends on the clinical condiron of the patient. In general enteral route is preferred, since it is more physiological; however, in certain condition where enteral route is either impossible or dangerous, parenteral nutrition can be used as an alternative which might be life saving. The advantages and disadvantages of nutritional support delivery is discussed briefly and comprehensively.The goal of nutritional support is to maintain or replete lean body mass, to support host defense mechanisms, to avoid specific nutritional deficiencies, and in general to improve clinical outcome in a malnourished patient or in at risk to develop mal- nourishment. Nutritional support can be instituted by enteral or parenteral route; each has its advantages and disadvantages. Which mode of delivery is chosen much depends on the clinical condiron of the patient. In general enteral route is preferred, since it is more physiological; however, in certain condition where enteral route is either impossible or dangerous, parenteral nutrition can be used as an alternative which might be life saving. The advantages and disadvantages of nutritional support delivery is discussed briefly and comprehensively.